FORMATION OF CRITERIA OF THE ANTI-DISCRIMINATION ANALYSIS OF SCHOOL TEXTBOOKS IN THE UKRAINIAN EDUCATIONAL FIELD - Voyevutko, Natalya; Kuligina, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This scientific work is aimed to develop the criteria of conducting the anti-discriminatory analysis of school textbooks based on the performed research. The work specified the normative, legal, scientific and methodical bases of gender and anti-discrimination analysis. The anti-discrimination requirements to the content of textbooks developed by the Ministry of Education and Science of Ukraine, the formation of gender expertise, and its reformatting into anti-discrimination one were analyzed. Authors of the work suggested the criteria of anti-discriminatory analysis that form a system combining the qualitative and quantitative factors in the evaluation of parameters, which are components of content of the textbook.